Outdoor Environmental Radiation Monitoring and Estimation of Radiation Risk on Public in New Market Thana, Dhaka, Bangladesh - Sumi, I. K.; Rahman, M. S.; Sakib, K. N.; Tasnim, M. M.; Yeasmin, S. (Journal of Scientific Research, 2021)
The Real-time outdoor environmental gamma radiation (RTOEGR) dose rates were monitored at New Market Thana in Dhaka city to generate a baseline database that would help to know any deviation after operation of Rooppur NPP. The RTOEGR monitoring was carried out using a digital portable radiation monitoring device (DPRMD). The RTOEGR dose rates at the area of New Market Thana were ranged from 0.103 ± 0.004 µSv/h to 0.168 ± 0.007 µSv/h with an average of 0.135 ± 0.004 µSv/h. The public's annual effective doses were calculated based on RTOEGR dose rates, and those were varied from 0.181 ± 0.007 mSv to 0.295 ± 0.007 mSv with an average of 0.238 ± 0.007 mSv. Excess Lifetime Cancer Risk (ELCR) on public health was estimated based on the annual effective dose. The Public's ELCR were from 0.720×10-3 to 1.174×10-3 with an average of 0.892×10-3, which is higher than the worldwide standard value of 0.29×10-3. The mean RTOEGR dose rate of the New Market Thana in Dhaka city is comparable to that of Sabzevar city (Iran), Kathmandu city of Tribhuvan University (Nepal), Baghdad city (Iraq), Kirikkale city (Turkey).